Efficacy and safety of ultrasound-guided bleomycin combined with dexamethasone in the treatment of pediatric lymphangiomas - Zhang, Yu-Tong; Zhang, Chao; Wang, Yu; Chang, Jian (Frontiers in Pediatrics, 2022)
Purpose This work aimed to report our experience with ultrasound-guided instillation for the treatment of lymphangiomas in children, so as to determine whether the combined use of bleomycin and dexamethasone achieved a higher response rate and a lower side effect rate. Methods The medical records from patients with lymphangiomas between January 1st, 2013 and September 31st, 2020, were reviewed. Patients who received bleomycin combined with dexamethasone sclerotherapy were classified as the dexamethasone group, while those receiving bleomycin without dexamethasone were classified as the control group. Results Altogether one hundred and twenty-seven patients were diagnosed with lymphangiomas. Among them, one hundred and five patients received bleomycin combined with dexamethasone injection, while the remaining twenty-two received bleomycin injection alone. The excellent rates were 89.52% [95% confidence interval (CI), 81.64% to 94.40%] in the dexamethasone group and 72.73% (95% CI, 52.51% to 92.94%) in the control group (p<0.05). Additionally, the recurrence rates were 3.81% (95% CI, 1.22 % to 10.03%) in the dexamethasone group and 13.64% (95% CI, 3.6% to 36.0%) in the control group (p>0.05). After comparison between the two groups, the following risk factors were identified. These include greater than ten sacs at the initial stage of diagnosis, larger size after all injections, and response to the first injection. Conclusions Although there was no significant difference in the recurrence rate between the two groups, this retrospective study demonstrated that the excellent response rates were dramatically improved between the two groups, suggesting that bleomycin combined with DEX was an effective and highly safe treatment for all types of pediatric lymphangiomas. Moreover, this study also identified three novel features as the significant risk factors for recurrence.